(untitled) (Journal of Kathmandu Medical College, 2013)
Background: Depressive disorder is frequently found as a comorbidity among patients with substance abuse. Most of the time it is reported as underdiagnosed and a majority of patients go untreated. Many studies have indicated that comorbid depressive symptoms play a major role in the prognosis of substance use disorder and the relapse has been found to be greater in patients who have a comorbid depression. The present study seeks to determine the comorbidity of depression in cases with substance abuse and their sociodemographic characteristics. Objective: The current study is aimed to determine the relationship between various drug abusing patterns and comorbidity of depression with substance use disorders. Methods: This was a cross-sectional study. The study was carried out in 42 patients, who were consecutively admitted in psychiatric ward of Kathmandu Medical College Teaching Hospital and Punarjeevan Hospital with the diagnosis of mental and behavioural disorder due to use of psychoactive substances, according to ICD-10. The study was carried out from 1st January 2010 to 30th December 2010. All patients were rated using Hamilton Depression Rating Scale. Results: Among all subjects, 31 (73.8 %) were found to be suffering from Depression among which 19 (45.2%) had mild to moderate depression and 12 (28.6%) had severe depression. Depression was seen among 80% of unemployed subjects, followed by 75% employed subjects and 68.8% students. In method of drug intake, 21 (50%) subjects used oral drugs, 12 (28.6%) subjects used intravenous route and 5 (11.9%) subjects used inhalational drugs. All patients using intravenous drugs were found to have depression. Among drugs abused, 22 (52.4%) patients used multiple substances like alcohol and cannabis, 11 (26.2%) patients used Heroin, 6 (14.3%) patients used drugs like Diazepam, Dextropropoxyphene, Nitrazepam and Promethazine, followed by 3 (7.1%) patients using Buprenorphine. Depression was found in 6 (54.54%) out of 11 subjects who used Heroin followed by 19 (86.63%) out of 22 subjects who were dependent on alcohol, cannabis and other substances. Conclusion: The result showed strong correlation between depressive symptoms and substance abuse, which draws attention to the need of taking into consideration the comorbidity and its management. Clinicians should routinely assess for depression in patients with substance abuse disorders. DOI: http://dx.doi.org/10.3126/jkmc.v1i2.8145 Journal of Kathmandu Medical College, Vol. 1, No. 2, Oct.-Dec., 2012: 96-99